Strategi Branding Pondok Pesantren Ath-Thohiriyyah Purwokerto dalam membangun Ekuitas Brand di Era Digital - Aedi, Ulul (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
This article aims to reveal the branding strategy of the Ath-Thohiriyyah Islamic Boarding School in building Brand Equity in the Digital Era using the Brand Resonance approach. The position of this article is to strengthen previous theories about Islamic boarding school branding by using a different approach. This descriptive qualitative research with data collection techniques using interviews. Interviews were conducted with the caretaker's family, administrators, community and alumni. Observation reveal posts on social media. While documentation is used to document the data obtained. The result of this article is that the Ath-Thohiriyyah Islamic boarding school is able to build and even develop its brand equity by making effective use of social media in the current digital era. Ath-Thohiriyyah Islamic Boarding School uses Brand Resonance elements in its branding activities, in the form of brand salience, brand performance, brand image, brand judgment, brand feeling, and Brand Resonance.